Metabolic signatures of combined exercise and fasting: an expanded perspective on previous telomere length findings - Almuraikhy, Shamma; Naja, Khaled; Anwardeen, Najeha; Sellami, Maha; Al-Amri, Hadaia Saleh; Al-Sulaiti, Haya; Bashraheel, Sara S.; Aden, Amina Ali; Elrayess, Mohamed A. (Frontiers in Aging, 2024)
IntroductionAging is a complex process marked by a gradual decline in physiological function and increased susceptibility to diseases. Telomere length is frequently regarded as one of the primary biomarkers of aging. Metabolic profiles are key features in longevity and have been associated with both age and age-related diseases. We previously reported an increase in the telomere length in healthy female subjects when Ramadan fasting was combined with physical training. This study aims to characterize the metabolic signature differentiating the combined effects of exercise and fasting from exercise alone and explore the correlations with the previously reported telomere length changes.MethodsTwenty-nine young, non-obese, and healthy female subjects were previously randomized into two groups: one group followed a 4-week exercise program, while the other group followed the same 4-week exercise program but also fasted during Ramadan. Metabolic profiles were assessed pre- and post-intervention using untargeted metabolomics.Results and DiscussionOur results showed a significant decrease in many lipid metabolites in the exercise-while-fasting group, particularly ceramides. Our study sheds light on the dynamic changes in lipid metabolism and its potential role in inflammation and age-related diseases, and contributes to the broader understanding of how lifestyle factors can influence cellular aging and metabolic health.